Symmetric Reverse Gamma *-4-Centralizers on Semiprime Gamma Rings with Involution - Ikram Saed (Al-Qadisiyah Journal of Pure Science, 2021)
Let M be a -ring with involution . In this paper , we will introduce the concept of symmetric left(right) reverse *-4-centralizer of M . Then, we proved that the  4-additive mapping  T:MxMxMxMM is a reverse *-4-centralizer of M under certain conditions .